Some comments about the existing theory of sound with comparison to the experimental research of vector effects in real-life acoustic near fields - WEYNA, Stefan (Archives of Acoustics, 2007)
Classical studies on the descriptions of acoustic field in an area of a near field, in accordance with the relations formulated by Kirchhoff, Huygens or Rayleigh's integral formula, are commonly known. It is also known that typical interference phenomena, such as diffraction and scattering of acoustic waves, appear in an acoustic field of the real sources as a result of mutual reactions of component waves. Today these vector effects of the acoustic wave occurring in the area of a near field can be simple measured directly with the use of a sound intensity technique.This article presents a few examples of the application of a sound intensity technique to the graphic presentation of the spatial distribution of the acoustic power flow over various geometrical shapes of structures located in a three-dimensional half space. The results of these studies contribute to the theory of sound and general knowledge about the physics of flow acoustic phenomena, especially in the near acoustic field. As a result of research, the visualization analysis of the sound intensity flux in 3D space is shown. The visualization of acoustic power flow in real-life acoustic fields can explain many particular energetic effects (scattering, vortex flow, shielding area, etc.), concerning areas where it is difficult to make numerical analysis.